THE IMPLICATIONS OF GREEN ACCOUNTING ON PROFITABILITY: A STUDY OF MINING COMPANIES IN INDONESIA - Felsa Finda Puspita M; Imelda Dian Rahmawati (Antis Publisher, 2025)
Objective: This study aims to determine the effect of Green Accounting, Environmental Dimensions, and Intellectual Capital on Profitability (ROA). Method: This study employs quantitative methods and secondary data sources, focusing on mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The sampling technique used was purposive sampling, which is a technique of sampling based on specific criteria, resulting in 20 companies with a total of 60 sample data. Data analysis was performed using the SPSS 25 software for multiple linear regression. Results: The results of the study indicate that: (1) Green Accounting does not affect Profitability, (2) Environmental Dimension does not affect Profitability, and (3) Intellectual Capital has a positive effect on Profitability in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Novelty: The novelty of this study lies in its examination of Green Accounting, Environmental Dimensions, and Intellectual Capital simultaneously in relation to Profitability (ROA) within mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period.